An Introduction to the Continental Record of the Laurentide Ice Sheet - St-Onge, Denis (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1987)
ABSTRACTThe record of the Laurentide Ice Sheet is not well preserved in terrestrial deposits. Sediment sequences are incomplete and few record events older than the last ice retreat. Furthermore, in the absence of absolute dating methods for deposits older than the limit of radiocarbon dating, units are generally assigned a chronostratigraphic position by "counting from the top". As a result age estimates of many units can differ significantly between authors.